Estimasi Sumberdaya Batubara Dengan Menggunakan Metode Ordinary Kriging Pada Pit X Di PT Selamat Jaya Job Site Puteri Hijau Kecamatan Puteri Hijau Kabupaten Bengkulu Utara Provinsi Bengkulu - Dian Nur Ikhsan; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. PT Selamat Jaya is a coal contracting company located in Puteri Hijau sub-district, Bengkulu Utara District, Bengkulu Province. PT Selamat Jaya has 2 work locations, namely PT Bara Mega Quantum and PT Kaltim Global. The research area of the researcher is PT Katim Global. Where in the Mining Business Permit area, PT Kaltim Global has a newly opened pit and is nearing completion for the initial coal mining stage. To increase production, it is necessary to develop the pit area. PT Selamat Jaya with the owner of PT Kaltim Global does not yet have a resource sediment model, so estimation of coal resources is needed. This process aims to estimate the amount of coal tonnage and how coal deposits are spread below. In this study, the method used to estimate coal resources is the ordinary kriging method. From the estimation results using this ordinary kriging method, later sediment models from coal will be obtained including the amount of coal tonnage. The total coal tonnage in the study area was 10.274.544 tons, with a covering layer of 41.088.000 Bcm. From the calculation we also got a stripping ratio of 1 : 3,9.Keywords : Coal, estimation, ordinary kriging , sediment model, resources